University Students' Research Skills and Covid-19 related article: an insight of the importance of strategically building research skills (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2022)
Skills in conducting research are skills that are very necessary for both prospective teachers and prospective scientists. By using the results of research related to community readiness in carrying out the Covid-19 vaccination, the research abilities of prospective teachers and students majoring in natural sciences are identified. Prerequisite lectures and student grades in these courses have a significant influence. In addition to developing through prerequisite courses, strategic research skills development also needs to be done by making scientific articles the backbone of learning.
Keywords: covid-19 vaccination; assured readiness; conditional readiness; mandatory readiness